Internet of Things: A Monitoring and Control System for Rockmelon Farming - Mad Kaidi, Hazilah; Ahmad, Norulhusna; Dziyauddin, Rudzidatul Akmam; Mohamed, Norliza; Abdul Latiff, Liza; Usman, Sahnius; Ahmad, Robiah; Sarip, Shamsul (International Journal of Integrated Engineering, 2020)
This paper describes the internet of things application in agriculture production especially for rock melon farming. In order to boost agricultural production on a commercial basis, a more systematic approach should be developed and organized to be adopted by operators to increase production and income. This work combines fertilization and irrigation in one system under protective structures to ensure that high-quality plant production and an alternative to conventional cropping systems. In addition, the use of technology for online monitoring and control is an improvement to the system in parallel with the rapid development of information technology today. The proposed system is focusing on automation, wireless, data analytics and simplified design with minimal and scalable skid size for rock melon in the Klang valley. Other than that, a monitoring and control system were developed besides, applied Internet of Thing (IoT) platform with additional user-friendly programmable farming routine Human-machine interfacing (HMI). HMI is a software interface that is capable to conduct the systems directly via autonomous cloud control. It provides time management and contributes to a more efficient workforce. The aim to develop a monitoring and controlling system using IoT for rock melon in this study was achieved. The rock melon harvesting succeeds according to the scheduled routine and the quality of yields also satisfied.